PEACE EDUCATION AND CONFLICT MANAGEMENT FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Mahuta, Muhammad G. (Sokoto Educational Review, 2020)
Education is said to be everybody’s right and it should be accessible to every individual in the society, regardless of ethnic, socio-economic, gender and geographical inclinations. In this regard peace is also every body’s right and peace education should be the major panacea to all social conflicts in the society. This paper focuses on the issues of conflict, conflict management and the possible means of promoting peace through conflict management strategies. The problems and causes of conflicts are discussed and the use of peace education for conflict management is examined for the promotion of sustainable development. Thus, peace education is identified as an effective tool for conflict management and sustainable development in the society. Lastly, the paper made some recommendations on the use of peace education and conflict management for the achievement of sustainable development in Nigeria.